Piebaldism in To Balo, South Sulawesi: Brief Report and Literature Review - Cut Muthiadin; Isna Rasdianah Aziz; Andi Nabila Nurfitrah; Pujarena Putri Idris (Universitas Islam Negeri Mataram, 2019)
Piebaldism is an autosomal dominant congenital disorder in pigment as a result of mutations in KIT gene, mapped on the long arm of chromosome 4. To Balo lived as a carrier of piebaldism genes. There are only four individuals of To Balo communities remained on Pujananting district, South Sulawesi. This study was a brief report and literature review about suspects of Piebaldism in To Balo. Data was collected by observation of depigmentation, interview and then depicted in pedigree. Phenotypic observations resulted in piebaldism on three individuals of To Balo, showed the same pattern and location of white patches. It is concluded that normal individuals could appear in third-generation when a woman or man carrier of piebaldism married with a normal individual.